Topological Optimization of Dynamic Stiffness in Continuum Structure Based on Bidirectional Evolutionary Structural Optimization - JIANG Xudong; LIU Zheng; TENG Xiaoyan (Journal of Harbin University of Science and Technology)
By minimizing structural dynamic compliance, the programming scheme of optimal stiffness for continuum structure under dynamic load is proposed, by combination of Equivalent Static Loads with Bidirectional Evolutionary Structural Optimization To effectively decrease calculation scale for dynamic optimization in structural topology, the Equivalent Static Loads Method is applied to transforming dynamic optimization to static one that is solved by Bidirectional Evolutionary Structural Optimization in structural topology To enhance the optimal efficiency of the original BESO method to optimization of dynamic stiffness in continuum structure, a design domain reduction method is developed to establish a new volume control and a stop criterion in this study Numerical results show that the dynamic compliance is asymptotically convergent to optimal solution with volume constraint precisely 〖JP3〗satisfied, and optimal configuration can effectively inhibit the vibration induced by dynamic load Whereby the presented optimization algorithm is verified to be robust and adapt Consequently it is provided with theoretical significance to extend the original Evolutionary Structural Optimization Method to dynamic optimization in structural design